EFEKTIVITAS KONSELING MOTIVATIONAL INTERVIEWING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA BROKEN HOME DI SMP NEGERI 1 PELAIHARI - Anisah, Laelatul; Aminah, Aminah; Farial, Farial (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
Motivation is an important thing in the learning process. The existence of student motivation in learning will make the learning process more enjoyable, communication smoother, reducing student anxiety, increasing creativity and learning activities. Mc. Donald in Sardiman (2008: 73) argues that motivation is a change in energy in a person which is characterized by the appearance of "feeling" and preceded by a response to the existence of goals. With the high motivation to learn, students will be able to achieve optimal self development in their learning achievement which is one of the main goals in learning. Based on the results of a discrete analysis of the percentage of learning motivation after providing individual counseling services with motivational interviewing techniques has increased. The average level of broken home student learning motivation in SMP Negeri 1 Pelaihari becomes 66.11% in the high category, where 64% or 23 people with a high enough category and 36% or 13 people in the Medium category and no longer found students who are at low category. From the results of the data processing, it is known that there is an increase of 10.53% where in the preservice delivery the motivation level is an average of 55.58% to 66.11%. This proves that after providing individual counseling services with motivational interviewing techniques student learning motivation can increase. Besides that based on the results of the hypothesis analysis test data obtained t count = 11.51 and t table = 1.994, so t arithmetic> t table .. This shows that "there are differences in the level of student motivation before and after getting individual counseling services with techniques motivational interviewing ".